2013
DOI: 10.1098/rsta.2012.0412
|View full text |Cite
|
Sign up to set email alerts
|

Water security, global change and land–atmosphere feedbacks

Abstract: One contribution of 16 to a Theme Issue 'Water security, risk and society' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…These gaps are partially due to inherent complexity in modeling Earth system processes, which is more significant in coupled simulation modes. Apart from various computational barriers, one main challenge in online simulations is the uncertainty associated with coupling land and atmospheric models, as given a unique land-surface boundary condition, the simulations obtained by different climate models can be divergent (Koster et al, 2004;Pitman et al, 2009;Dadson et al, 2013). Another major challenge for coupled irrigationland-surface-climate simulations is the choice of appropriate temporal and spatial resolutions, at which the relevant physical processes and feedbacks between land and atmosphere should be represented and described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These gaps are partially due to inherent complexity in modeling Earth system processes, which is more significant in coupled simulation modes. Apart from various computational barriers, one main challenge in online simulations is the uncertainty associated with coupling land and atmospheric models, as given a unique land-surface boundary condition, the simulations obtained by different climate models can be divergent (Koster et al, 2004;Pitman et al, 2009;Dadson et al, 2013). Another major challenge for coupled irrigationland-surface-climate simulations is the choice of appropriate temporal and spatial resolutions, at which the relevant physical processes and feedbacks between land and atmosphere should be represented and described.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, irrigation can disturb the "natural" atmospheric boundary conditions (e.g., Sacks et al, 2009;Destouni et al, 2010;Gerten et al, 2011;Pokhrel et al, 2012;Hossain et al, 2012;Guimberteau et al, 2012;Dadson et al, 2013). At this stage of model development, the available quantitative understanding of these landatmospheric implications is limited.…”
Section: Modeling Human-water Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal control on run-off generation is the partitioning of rain water at the ground level between green and blue water flows. This partitioning is easily disturbed by land-use change and can alter consumptive water use through evapotranspiration [51]. L'vovich & White [52] showed that the global-scale deforestation during the period 1680-1980 for development of agriculture reduced vapour flow and increased run-off generation by the order of 2500 km 3 yr −1 .…”
Section: (B) Gradual Changes In Rainwater Partitioningmentioning
confidence: 99%
“…In parallel, a considerable proportion of the surface water diverted into irrigated areas may recharge groundwater (Döll et al, 2012). From a broader perspective, groundwater aquifers (particularly shallow groundwater) can also be an important control on soil moisture and wetlands, and thus influence atmospheric surface boundary conditions (e.g., Maxwell et al, 2007Maxwell et al, , 2011Fan and Miguez-Macho, 2011;Dadson et al, 2013). These online effects are widely unquantified at the global scale, as the sub-surface processes below the root zone have been generally assumed to be disconnected from the atmosphere (see Taylor et al, 2013).…”
mentioning
confidence: 99%